Przyczynek do biografii Ireny Sendlerowej (z dokumentów warszawskiego Ratusza) - Grabowski, Jan (Zagłada Żydów. Studia i Materiały, 2014)
The article presents several documents from the files of the war-time mayor of Warsaw, which concern the incarceration of Irena Sendler, the well-known rescuer of the Jews.